PENGARUH HIPNOTERAPI TERHADAP STRES BELAJAR DALAM MENINGKATKAN MOTIVASI BELAJAR MAHASISWA DI SEKOLAH TINGGI ILMU KESEHATAN KOTA MEDAN - Muhammad Taufik Daniel Hasibuan; Hendry Kiswanto Mendrofa (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2019)
Abstract Effective learning is important for an education and is the first step towards student development. Education demands that must be undertaken will be the triggering factors of the problems faced by students and academic problems related to learning stress and will ultimately affect student motivation. When there is a mismatch between demands and the ability to deal with it can cause problems such as stress, and stress learning is a problem that often occurs in the educational environment. Hypnotherapy is a therapy that can overcome learning stress, increase learning motivation, improve bad habits and can also strengthen memory. The purpose of this study was to determine the effect of hypnotherapy on learning stress in increasing student motivation. This type of research uses a quasi-experimental design with one group pre-post-test test. The sample used in the study amounted to 35 people and the sampling technique used consecutive sampling. Research data collection using the SLSI instrument and learning motivation instruments, as well as data analysis used using the dependent t-test. From the results of the statistical test of the dependent t-test between before and after the intervention on learning stress we found a significant difference (t=17,198, p=0,000) and on learning motivation (t=10,345, p=0,000), it can be concluded that effective hypnotherapy reduce learning stress and increase student motivation. The use of hypnotherapy can help the achievement of effective learning and maximize the potential for better learning for students and suggest its use in the educational environment. Keywords: Hypnotherapy, learning stress, learning motivation